2017
DOI: 10.1016/j.chiabu.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment, psychopathology and well-being: The mediator role of global self-esteem, attachment difficulties and substance use

Abstract: Printed by NTNU Grafisk senter 1 NORSK SAMMENDRAG Ungdom i risiko: Overgrepserfaringer, psykopatologi og livskvalitet blant ungdom i barnevernsinstitusjonerOvergrep og omsorgssvikt i barndommen er assosiert med en rekke fysiske og psykiske helseplager senere i livet. Å kunne identifisere risikoutsatte befolkningsgrupper er svaert verdifullt med tanke på å kunne forebygge helseplager. Barn og unge i fosterhjem og på barnevernsinstitusjoner har opplevd mer overgrep og omsorgssvikt enn barn og unge i normalbefolk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 116 publications
(187 reference statements)
1
31
0
6
Order By: Relevance
“…Some theorists have pointed out that large amounts of negative events would lead to learned helplessness, which might lead to low self‐esteem 33 . Additionally, abundant empirical studies have found a positive association between childhood maltreatment and low self‐esteem 34,35 . Thus, we proposed:
H3: People who are maltreated would have lower self‐esteem.
…”
Section: Relevant Literature and Hypotheses Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Some theorists have pointed out that large amounts of negative events would lead to learned helplessness, which might lead to low self‐esteem 33 . Additionally, abundant empirical studies have found a positive association between childhood maltreatment and low self‐esteem 34,35 . Thus, we proposed:
H3: People who are maltreated would have lower self‐esteem.
…”
Section: Relevant Literature and Hypotheses Developmentmentioning
confidence: 93%
“…33 Additionally, abundant empirical studies have found a positive association between childhood maltreatment and low self-esteem. 34,35 Thus, we proposed:…”
Section: Childhood Maltreatment and Self-esteem And Envymentioning
confidence: 99%
“…Research has consistently demonstrated that maltreated children have higher rates of insecure attachment, namely disorganized attachment, relative to non-maltreated children, even when compared to other high-risk children (e.g., [71]). Similarly, maltreated children have been consistently found to be at heightened risk for future substance use issues [72,73,74], with effects persisting into middle adulthood for females only [29,30,31,32]. Children classified as having disorganized attachment often vacillate between avoidant and anxious parent-child behaviors due to conflicting and unpredictable caregiver responses; these children often have poor outcomes across many domains, including lower academic achievement and self-esteem, poor peer interactions, atypical classroom behaviors, cognitive immaturity, and externalizing behavioral concerns (e.g., [70]).…”
Section: Origins Of Substance Use In Women Exposed To Ipvmentioning
confidence: 99%
“…La satisfacción con el propio aspecto físico (Mccoy et al, 2014;Rosés Gómez et al, 2015;Silverthorn et al, 2017), el rendimiento académico (Zuffianò et al, 2013), el bullying o ciberbullying (Scott & Dale, 2016;Vlachou et al, 2011;Voloschin, Becerra, & Simkin, 2016), el maltrato infantil (Edwards et al, 2003;Greger et al, 2017), el trabajo infantil (Ávila, 2007), o las adicciones en la infancia (Kounenou, 2010) Neuroticismo pueden asociarse negativamente a la autoestima (Piedmont, Sherman, & Sherman, 2012). En relación a la espiritualidad se observan vínculos positivos con la autoestima, esto podría deberse a que la autotrascendencia espiritual tiende promover el desapego, permitiendo desalienarse de los ideales establecidos y permitiendo aceptar la vida y los otros tal cual son (Coholic, 2005;Simkin & Azzollini, 2015;Simkin & Etchevers, 2014).…”
Section: La Centralidad De Los Eventos Traumáticosunclassified